Avoiding leukocyte contamination and early platelet activation in platelet-rich plasma. - Trindade-Suedam, Ivy K; Leite, Fábio R M; de Morais, Juliana A N D; Leite, Elza R M; Marcantonio, Elcio Júnior; Leite, Amauri A (American Academy of Implant Dentistry, 2007)
The objective of this study was to describe a new platelet-rich plasma (PRP) protocol with a reduced concentration of leukocytes and intact platelets. We collected 8 mL of venous blood (VB) from marginal ear veins of 10 male New Zealand white rabbits in acid dextrose citrate Vacutainer tubes. Tubes were centrifuged at 302g for 10 minutes. All plasma was collected in plastic tubes to avoid buffy-coat contamination and centrifuged at 2862g for 5 minutes. A 10% calcium chloride activator (10 PRP:2 CaCl2) was added to the lower third of this plasma (PRP), and the PRP gel was obtained. Mean platelet count was 317.7 x 10(3) +/- 39.9/microL in VB and 1344.9 x 10(3) +/- 347.5/microL in PRP. Leukocyte counts were 3.96 x 10(3) +/- 2.01/microL and 0.46 x 10(3) +/- 0.45/microL in VB and PRP, respectively. Mean platelet enrichment was 327.4 +/- 97.8%. All differences were statistically significant (P > .05). This protocol is practical and reproducible, resulting in a high concentration of intact platelets to help tissue repair and low levels of leukocytes.
Keywords: animal; centrifugation; cytology; leukocyte; leukocyte count; male; physiology; plasmapheresis; rabbit; thrombocyte; thrombocyte activation; thrombocyte count; thrombocyte rich plasma; Animals; Blood Platelets; Centrifugation; Leukocyte Count; Leukocytes; Male; Plasmapheresis; Platelet Activation; Platelet Count; Platelet-Rich Plasma; Rabbits